Intuitionism in Contemporary Polish Ethics. Part II. Elzenberg – Ingarden – Wojtyła – Styczeń – Przełęcki - Wiśniewski, Ryszard (Ruch Filozoficzny, 2020)
The article is a continuation of the comparative analysis of intuitionism in contemporary Polish ethics published in volume LXXV no. 3 (2019). It centres around the theoretical and cognitive foundations of ethics of Henryk Elzenberg, Roman Ingarden, Karol Wojtyła, Tadeusz Styczeń and Marian Przełęcki. These thinkers share an empirical starting point in the interpretation of moral cognition as the material for building philosophical ethics. They assume that moral experience is the cognitive basis of ethics, which requires its clarification, ordering and explanation in order to continue to justify it as far as possible. Individual differences between the thinkers lie in the attempts to legitimise the principles of ethics or the ethical ideal. Elzenberg, in his ambitious perfectionist understanding of ethics, falls into a pessimism and meta-empirical (metaphysical) mysticism. Ingarden seeks to explain the experience of moral values in ontology, but his attempts have not gone further than an anthropological turn (towards examining the ontological foundations of responsibility). Wojtyła found an explanation for the experience of morality in anthropology of the person fulfilling himself in action, assuming the metaphysics of the identity of being and value in the background. Styczeń, for the ultimate explanation of the experience of obligation of a person’s affirmation indicated the metaphysics of the justifying ‘Necessary Reason’ to be the basis of a universal ethical norm, and subsequently the anthropology of man and truth. He treats ethics as an empirical science based on moral intuitions, but in an attempt to explain it, he refers to the metaphysics of neighbour. The article demonstrates that basing ethics on moral experience is usually connected with the notion of moral experience that is emotional, and directed objectively to a value connected with the experience of obligation. Although moral intuitions are not apodictic at the starting point (the possibility of error is assumed), but open to the cognitive work of the intellect, at the end of the path of ethical cognition, in a manner that is more or less clear, the analysed thinkers refer to intuition in a different, often universalising, perspective that is anthropological, metaphysical, or mystical.